Peningkatan Kemampuan Kepemimpinan Digital (Digital Leadership) Bagi Aparatur Pemerintah Desa Sumberejo Kecamatan Madiun Kabupaten Madiun - Yunas, Novy Setia; Kuswandoro, Wawan Edi; Susanto, Amin Heri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The development of technology and information is now growing so fast in all aspects of human life, including aspects of Government. So important and strategic is the existence of technology in the midst of the current era of disruption that ultimately brings demands for the need for digital transformation at all levels of Government, both at the Central, Regional and Village levels. Digital transformation in the Government sector is not easy, let alone the Village Government level. There are many challenges that must be overcome to move towards a fundamental change process in the use of technological instruments for government, ranging from human resources, policy support, budget, technology infrastructure and most importantly political commitment. To realise this, digital leadership skills are needed for all village government officials from the leadership level to the executor. Digital leadership is currently needed because a leader and existing apparatus are required to have the ability to respond to and understand the development of technology and information that is accelerating so quickly. The FISIP UB Internal Community Service activity entitled Strengthening the Capacity of Digital Leadership for the Sumberejo Village Government Apparatus, Madiun District, Madiun Regency is a community service activity designed with the aim of increasing the competence and ability of digital leadership in leaders, village officials and digital cadres in the village, encouraging efforts to accelerate digital transformation in the village by maximising the potential of existing human resources in the village and increasing community participation in development processes and creating innovations based on digital technology at the village level. This article is the result of community service activities carried out through 3 stages, namely first, the preparation stage which includes target mapping activities as well as presenters of community service activities focused on all village officials and digital cadres in the village. second, the socialisation stage in order to equalise perceptions and ensure that the target group as workshop participants have digital awareness and a clear understanding of the purpose, content, and benefits of this activity. Third, the implementation stage where the target group consisting of the Village Head, Village Secretary, BPD, Village Government, Babinsa and Bhabinkamtibmas as well as digital cadres in the village received direct guidance from professional speakers on digital technology, digital transformation, public service innovation and how to build digital leadership capabilities in the current era.